UJI DAYA HASIL BEBERAPA VARIETAS KEDELAI DALAM TUMPANGSARI DENGAN JAGUNG PADA EMPAT TIPE AGROEKOSISTEM LAHAN KERING DI PULAU LOMBOK NUSA TENGGARA BARAT - fakultas pertanian unram; idris pemuliaan; I GM. Arya Parwata (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2018)
ABSTRACT The aims of this reseaarch were to know : i) yield ability of varieties of soybean planted in multiple cropping with mayze in four types of agroecosystem; ii). Adaptive ability and yield stability, and genetic variability of quantitative traits. The research used Randomized Completely Block Design with eight varieties of soybean, such as : Tampomas, Merapi, Jayawijaya, Willis, Rinjani, Cikuray, Galunggung and Lokon, multiple cropped with mayze var. Arjuna Willis variety as control. The experiment was carried out in four types of agroecosystem, such as : upland depended on the rain, upland irrigated by pump well, dryland after cultivating “gogorancah” rice, and dryland irrigated by high Level Diversion system. The results of the experiment showed that : the types of agroecossystem did not affect on the qualitative traits; the yield ability of Tampomas, Lakon, Jayawijaya, Rinjani, Cikuray and Galunggung is same as Willis but Merapi was lower than it in dryland irrigated by high level diversion system; There is no stable and adative varieties. Tampomas, Jayawijaya and Galunggung varieties were only able to adaptive in productive agroecosystem, but Cikuray and Lokon only adapted specially in marginal condition; The highest variability of harvesting day, number of productive branch and dry seed yield were in the land irrigated by hight level diversion system; plannt height, number of pod, number of filled out of pod were in upland irrigated pump well; weight of 100 dry seeds was in the dryland depended on the rain after cultivating “gogo rancah” rice.